Pengaruh Konsumsi Urin Sapi Bali Terhadap Kadar Blood Urea Nitrogen, Kreatinin Serta Gambaran Histopatologi Ginjal Tikus - Alunat, Desi Elrini Sarah; Kardena, I Made; Suarsana, I Nyoman (Buletin Veteriner Udayana, 2014)
This study was conducted to determine the effect of bali cattle urine consumption to blood urea nitrogen and creatinine levels and  histopathological observation on rat kidney. A total of 20 male white rats were used in this study. They were divided into 4 groups : K1 was given distilled water and feeded libitium, while K2,K3,K4 were given bali cattle urine at dose 0,5; 1; and 2 cc/head/day for 30 days respectively. At the end of the treatment period, the all rats were euthanized with cetamine and Blood was collected to obtain plasma. Plasma was analyzed on the content of blood urea nitrogen, and creatinine. Kidneys was taken for histopathological ??with hematoxylin-eosin staining. The results showed that administration of bali cattle urine of a dose 2cc/head/day can lead to increased levels of blood urea nitrogen and creatinine. On the observation of kidne histopathology showed hemorrhage intertubular and fatty degeneration.
Keywords: Bali cattle urine, BUN dan creatine, kidney, Histopatology